A Landscape of Memories through the Music of Hope Lee - Feliz, Juro Kim (Nomadic Sound Worlds, 2018)
Produced by Juro Kim Feliz under the Canadian Music Centre Library Residency, Nomadic Sound Worlds is a four-part blog/podcast series exploring Canadian contemporary music through the lens of present-day global migration. A collection of essays named Letters of Transit: Reflections on Exile, Identity, Language, and Loss (ed. André Aciman, 1999) informs and inspires this project, with trajectories branching out from related themes including mobility, displacement, loss, reconciliation of polarized truths, and invention of selves. In this regard, the series will feature selected immigrant Canadian composers whose musical worlds collide with various personal stories of immigration.

Ana Sokolović. Robots musicaux et kolo serbe - Harman, Brian (La création musicale au Québec, 2018)

Their Own Agenda: The History, Development, and Culture of Women's Orchestras Outside the United States - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

Entrevista com a cantora e compositora Bïa Krieger [Entretien avec l'autrice-compositrice-interprète Bïa Krieger] - Cassiano, Raissa (Tradterm, 2018)
Radicada há mais de vinte anos na França e no Canadá, Bïa Krieger conquistou um público cativo nesses países, onde recebeu prêmios importantes, como o Grand Prix de l’Académie Charles Cros (França), Prix de l’Adisq (Canadá) e Félix du Meilleur Album Musiques du Monde (Canadá). Esta entrevista contempla o seu trabalho como versionista, com enfoque nas versões em francês para canções de Chico Buarque.

Aller à la quête de l’œuvre : Véronique Lacroix et les 30 ans de l’ECM+ - Champagne, Éric (Circuit : musiques contemporaines, 2018)

Diane Dufresne. Aujourd'hui, hier et pour toujours - Dufresne, Diane (Éditions Libre Expression, 2018)
Diane Dufresne est l'une des plus célèbres voix de la chanson québécoise et figure parmi les artistes les plus importantes de notre époque. Sa virtuosité et sa créativité est reconnue tant au Québec qu'en Europe. À soixante-quatorze ans, elle poursuit activement sa carrière. Sa popularité est immense et, au fil des ans, elle a reçu de nombreuses distinctions. Cet ouvrage, élaboré en collaboration avec son époux, l'artiste sculpteur Richard Langevin, propose une rétrospective d'un parcours riche en événements et en succès. De Tiens-toé ben j'arrive! à Magie rose en passant par Les Violons du Roy, ce livre relate les grandes étapes de la vie professionnelle et personnelle de la chanteuse à partir de photos souvenirs et d'images inédites. Un véritable devoir de mémoire.

Pauline Julien, intime et politique - Ferland, Pascale (Office national du film du Canada, 2018)
Suivant un minutieux choix d'extraits d'entrevues, de spectacles et de photos, puisés à même un colossal et riche fonds d'archives, Pauline Julien, intime et politique nous entraîne dans le sillage de cette femme résolument libre et engagée, figure emblématique de la chanson et d'une époque charnière de l'histoire du Québec.

La renarde et le mal peigné - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2018)
Dans ces « fragments de correspondance amoureuse », on découvre Pauline Julien et Gérald Godin comme jamais on ne les avait vus, comme jamais plus on ne les verra. Lui, jeune loup puis loup mature, passionné, dévoué à la cause et amoureux. Elle, mère, chanteuse, absente souvent, incertaine et amoureuse. Elle que le doute assaille, toujours. Lui, de plus en plus sûr. C’est un magnifique tango qui se déroule sous nos yeux, on s’attire et se repousse dans le même paragraphe. Et c’est beau. Que c’est beau! La poésie qui les habite en permanence est suffisante pour rendre n’importe quel esprit jaloux, suffisante pour affadir n’importe quel amour. Pascale Galipeau, fille de Pauline Julien, a dû braver objections et réprimandes pour publier ces lettres. On ne peut que la remercier à genoux et lui baiser les mains de ne pas avoir cédé.

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

L’intermédialité autochtone dans l’œuvre de Natasha Kanapé Fontaine : mémoire, oralité et territoire - Morin-Martel, Florence (Université de Montréal, 2018)
Ce mémoire explore la notion d’intermédialité autochtone au sein de l’oeuvre de Natasha Kanapé Fontaine. Les imbrications entre les médias seront notre point d’appui pour penser les questions de l’esthétique dans l’art autochtone actuel. Par le biais de la représentation d’un média dans un autre, nous aborderons ainsi la réactualisation des traditions orales telles que le conte, le mythe, le chant et le tambour au sein des productions de cette artiste. Notre parcours observera les structures intermédiales qui mettent en exergue la mémoire ainsi que les connaissances ancestrales. Les croisements entre l’identité et le territoire seront également discutés dans l’optique des représentations intermédiales. Ainsi, les phénomènes d’affirmation et de réactualisation des savoirs se déploient par l’utilisation de divers médias. De ce fait, la résistance environnementale et culturelle ainsi que la néo-oralité sous-tendent l’oeuvre de l’artiste et s’expriment à travers les territoires imaginaires et médiatiques.

Isabelle Panneton. De la rigueur à la liberté de création - Nattiez, Jean-Jacques (La création musicale au Québec, 2018)

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.

Alys vue par Rita - Savoie, Chantal (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Durant la Crise et la Deuxième Guerre mondiale, on imagine Montréal sans ressources pour la culture, Montréal ligotée, bâillonnée. C’est bien mal la connaître. Au contraire, elle s’engage alors dans une des grandes révolutions du siècle, soit celle des médias qui parlent et qui chantent. Le cinéma, la radio, le disque y recomposent l’environnement du divertissement et des arts d’une manière surprenante. Et ces nouveaux médias ne remplacent pas la presse, le concert ou le théâtre, ils s’y ajoutent, multipliant l’offre à un point qu’on n’avait encore jamais vu. Cela révolutionne la vie chez soi où, en plus du journal et du magazine, dont les tirages explosent, le piano rencontre deux nouveaux concurrents, le gramophone et le récepteur radio. Sans être riche, on peut entendre des concerts, même de musique autochtone et de grandes vedettes, chez soi, on peut « swinger » sur le jazz chez soi. On peut aussi sortir, ce que facilite un urbanisme stimulé par les nouvelles gares. Les salles de cinéma, de danse, se multiplient. C’est là qu’on se laisse emporter par le jazz ou « Tico, tico ». On se plaint chaque année que le théâtre se meurt ? Ça n’empêche pas une rencontre entre Shakespeare et Alfred Pellan. Ou d’aller entendre un transethnique prêcher l’écologie. Et aussi de s’habiller à la mode pour aller skier sur la montagne. Ce bouleversement transforme le visage de la ville, comme nous le révèlent les peintres juifs, les radioromans, ou deux œuvres majeures du temps, Two solitudes et Bonheur d’occasion. On ne verra plus jamais Montréal avec les mêmes yeux, on n’entendra plus jamais Montréal avec les mêmes oreilles. Avec des textes de Marie Beaulieu, Justin Bur, Marc H. Choko, Marie-José des Rivières, Dominic Hardy, Lorne Huston, Germain Lacasse, Laurier Lacroix, Marie-Thérèse Lefebvre, Renée Legris, Jocelyne Mathieu, Sandria P. Bouliane, Adrien Rannaud, Peggy Roquigny, Lucie Robert, Mario Robert, Denis Saint-Jacques, Chantal Savoie, Esther Trépanier et Elspeth Tulloch.